Recent Advances of Optical Tweezers–Based Dynamic Force Spectroscopy and Mechanical Measurement Assays for Live-Cell Mechanobiology - Wang, Haoqing; Guo, Yuze; Zou, Ran; Hu, Huiqian; Wang, Yao; Wang, Fan; Ju, Lining Arnold (Frontiers in Physics, 2022)
Cells sense and respond to mechanical stimuli for activation, proliferation, migration, and differentiation. The associated mechanosensing and biomechanical properties of cells and tissues are significantly implicated in the context of cancer, fibrosis, dementia, and cardiovascular diseases. To gain more mechanobiology insights, dynamic force spectroscopies (DFS), particularly optical tweezers (OT), have been further advanced to enable in-situ force measurement and subcellular manipulation from the outer cell membrane to the organelles inside of a cell. In this review, we first explain the classic OT-DFS rationales and discuss their applications to protein biophysics, extracellular biomechanics and receptor mediated cell mechanosensing. As a non-invasive technique, OT’s unique advantages in probing cytoplasmic protein behaviors and manipulating organelles inside living cells have been increasingly explored in recent years. Hereby, we then introduce and highlight the emerging OT rationales for intracellular force measurement including refractive index matching, active-passive calibration, and change of light momentum. These new approaches enable intracellular OT-DFS and mechanical measurements with respect to intracellular motor stepping, cytosolic micro-rheology and biomechanics of irregular-shaped nuclei and vesicles. Last but not least, we foresee the future OT upgrades with respect to overcoming phototoxicity and system drifting for longer duration live-cell measurements; multimodal integration with advanced imaging and nanotechnology to obtain higher spatiotemporal resolution; developing simultaneous, automated, and artificial intelligence inspired multi-trap systems to achieve high throughput. These further developments will grant unprecedented accessibility of OT-DFS and force measurement nanotools to a wider biomedical research community, ultimately open the floodgates for exciting live-cell mechanobiology and novel therapeutic discoveries.